TEKNIK DASAR DAN PERATURAN BOLA VOLI MAHASISWA FIKK UNM - Yadi Jayadilaga; Meliana Handayani; Nurul Fajriah Istiqamah; Sri Rezkiani Kas; Dian Anggraeni Rachman; A.Ulfiana Fitri (Universitas Maritim AMNI Semarang, 2023)
The game of volleyball in Indonesia is developing rapidly, volleyball is very popular with the public, both professionally and amateurs. Efforts to improve volleyball in the community with the aim of helping the federation optimize the potential of Indonesian youth. The problems faced by partners are mastery of basic techniques that are not yet optimal and knowledge of the rules and technology in ball games is still lacking. The solution offered is to provide basic technical mastery training and an introduction to rules and technology in volleyball games. Location of FIKK UNM volleyball field activities. Students as partners with a total of 35 people. This activity consists of theory and practice. Service activities run well and smoothly. Partners who are students feel happy and satisfied with the service activities carried out. We thank those who have helped carry out this dedication activity. Activities have had a positive impact on the development of volleyball.